Three new species of Drosophila tripunctata group (Diptera: Drosophilidae) in the eastern Andes of Ecuador - Ramos Guillín, Emily (2015)
Three new species of the Drosophila tripunctata group are described and illustrated. These new species were captured using plastic bottles containing pieces of fermented banana with yeast. The collections were from Napo Province, Ecuador at 2 200 m and 3 362 m above sea level. The new species are: Drosophila napoensis sp. nov., Drosophila cuyuja sp. nov. and Drosophila quijos sp. nov. The first two species belong to subgroup I and the latter species belong to subgroup III of the Drosophila tripunctata group.